Efektivitas Problem Based Learning Terintegrasi Focus Group Discussion Terhadap Kemampuan Berpikir Kritis Mahasiswa Pendidikan Biologi UIN Sunan Kalijaga - Gondo Adhi Saputra; Mahmud Arif; Sulistiyawati; Liza Jauharotul Munfarida Al Khurriyyah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to improve the critical thinking skills of first-semester students of the Biology Education Program at FITK UIN Sunan Kalijaga Yogyakarta through the implementation of the Problem Based Learning (PBL) model using the Focus Group Discussion (FGD) method. The study employed a quantitative approach with a pre-experimental design, specifically the one group pretest-posttest design, due to limited accessibility in conducting the research. The population consisted of 44 participants, including 9 male and 35 female students, selected using a convenience sampling technique. Data were collected through tests, and the analysis included normality tests, homogeneity tests, and hypothesis testing. The results showed that the average pretest score was 82.39 and the posttest score was 86.59, both categorized as high. The paired sample t-test revealed a Sig. (2-tailed) value of 0.001 < 0.05, indicating a significant difference between the pretest and posttest scores. Furthermore, the Cohen’s d effect size value of 0.5028 falls into the medium category, indicating a moderate effect. In conclusion, the implementation of the Problem Based Learning model through the Focus Group Discussion method effectively improves students’ critical thinking skills, as indicated by improvements in understanding (3.2%), analytical skills (4.12%), evaluation skills (4.62%), and problem-solving skills (5.04%). Keywords: Focus Group Discussion (FGD), Critical Thinking Skills, Biology Education Students, Problem Based Learning (PBL)